Local perceptions of trophy hunting on communal lands in Namibia. (February 2018) - Angula, Hilma N.; Stuart-Hill, Greg; Ward, David; Matongo, Greenwell; Diggle, Richard W.; Naidoo, Robin
Abstract: Trophy hunting in Africa is currently under pressure as some countries explore various policies that aim to put a halt to an activity that many people in the Western developed world view as unpalatable or unethical. However, in the debate over trophy hunting policy the voices of local communities, who in many instances allow wildlife to persist on the lands they control because of the tangible benefits they derive from it, have been largely unheard. Here, we report on an opportunistic survey of 160 rural residents of Namibia from 32 communal conservancies that generate varying levels of livelihood benefits from wildlife uses, including trophy hunting. About three quarters of these community members were employed in some manner by the conservancy. We used a mixed methods approach to assess community members' perceptions on trophy hunting, the benefits it generates, whether it was "good" or "bad", and how they would respond if trophy hunting were halted. 91% stated they were not in favour of a ban on trophy hunting, and only 11% of respondents would support wildlife on communal lands if a ban were in fact enacted. Most respondents (90%) were happy with trophy hunting occurring on communal lands due to the benefits it provides. These responses were consistent across respondent demographic categories, although those who stand to lose the most (i.e., those employed by or managing a conservancy), viewed trophy hunting in an even more favourable light. Our results suggest that in Namibia, a trophy hunting ban would be viewed very poorly by conservancy residents, and would seriously weaken their support for wildlife conservation. The imposition of trophy hunting policies by countries far from where rural land managers are conserving wildlife would not only restrict communities' livelihood options, but may have perverse, negative impacts on wildlife conservation.